2020
DOI: 10.1002/adfm.201908252
|View full text |Cite
|
Sign up to set email alerts
|

Nanogenerators with Superwetting Surfaces for Harvesting Water/Liquid Energy

Abstract: Water covers about 70% of the earth's surface and contains tremendous energy that remains untapped. Despite success in harvesting hydrodynamic energy based on heavy‐weight and bulky electromagnetic generators, a great deal of water energies stored in the low‐frequency flow of water such as in the form of raindrops, river/ocean waves, and the tide, remain largely untapped. In spite of diversity in development strategies and working mechanisms, engineering efficient water energy harvesting devices, especially na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
104
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(104 citation statements)
references
References 175 publications
0
104
0
Order By: Relevance
“…The latter has attracted substantial attention in recent years for its potential to directly convert energy from random environmental drop and contact line motion as in rainfall, spray, and surface waves to electrical energy [6,7,[9][10][11]. Numerous configurations of such "electrical nanogenerators" (ENGs) have been invented using one or two electrodes on a substrate typically connected to an external electric energy harvesting circuit with a load resistor [9,12]. The electrodes are covered by a hydrophobic dielectric layer that typically carries some permanent surface charges.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The latter has attracted substantial attention in recent years for its potential to directly convert energy from random environmental drop and contact line motion as in rainfall, spray, and surface waves to electrical energy [6,7,[9][10][11]. Numerous configurations of such "electrical nanogenerators" (ENGs) have been invented using one or two electrodes on a substrate typically connected to an external electric energy harvesting circuit with a load resistor [9,12]. The electrodes are covered by a hydrophobic dielectric layer that typically carries some permanent surface charges.…”
mentioning
confidence: 99%
“…However, unlike electrowetting where charges usually equilibrate much faster than the liquid, electrical and fluid dynamic processes in ENGs are more interwoven and their interplay has yet to be disentangled. In many ENGs, the water drops also fulfill a second role: in addition to providing the required initial mechanical energy, the impact process is also responsible for the generation of the trapped surface charge on the hydrophobic surface [6,9,12]. However, like other triboelectric charging mechanisms that have been explored, this process is notoriously difficult to control and dependent on details of materials and process conditions [16][17][18].…”
mentioning
confidence: 99%
“…Water covers 71.8% of the earth's surface and can be used as a sustainable energy resource. [ 1,2 ] Water can store gravitational and mechanical impact energy that can be converted into electricity through hydraulic power generation using electromagnetic generators. However, such electromagnetic generators are heavy, bulky, and immovable and are generally situated near dams, coasts, or river banks.…”
Section: Figurementioning
confidence: 99%
“…Water and electricity are fundamental to maintaining the regular operation of human society. [ 1,2 ] In this study, we demonstrated a prototype miniature SDMS that can utilize a low water supply, such as condensed water drops from fog, to generate electricity. SDMS showed stable and adjustable electrical responses to water dripping.…”
Section: Figurementioning
confidence: 99%
“…To overcome this limitation, Flu-TENG with liquid-solid interface has been proposed and studied extensively. [21][22][23][24][25] The Flu-TENG research up to now can be classified as dropletbased one and streaming flow-based one. Although many studies have been focused on the droplet because of simple structure and unambiguous working principle, there exists the restricted contact area and charge density in case of the droplet.…”
Section: Introductionmentioning
confidence: 99%